Expression of Hormonal Receptors (FSHR, ER-α, and PR) in Women with Pregnancy-Associated Periodontal Disease: A Molecular PCR-Based Study - Hafed, Noor Nemia; Al-Maamori, Jafar Abbas (American Journal of Biomedicine and Pharmacy, 2026)
Background: The response of gingival tissues and the susceptibility to inflammation are THUS1170 EX8524 MODERATED BY HORMONAL CHANGES. Detection of hormonal receptor (follicle-stimulating hormone receptor (FSHR), estrogen receptor alpha (ERα), and progesterone receptor (PR) genes in gingival tissues could be a crucial factor in the pathogenesis of periodontal disease. Objective To investigate molecular detection of follicle-stimulating hormone receptor (FSHR), estrogen receptor alpha (ER-α), and progesterone receptor (PR) genes among pregnant women with and without periodontal disease and compared to healthy non-pregnant women. Methodology: Gingival tissue samples were collected from three study groups: pregnant women with periodontal disease, healthy pregnant women, and non-pregnant control women. The presence of FSHR, ERα, and PR genes was analyzed using conventional PCR. Results: Altered detection patterns of hormonal receptors were observed in pregnant women with periodontal disease. Increased detection rates of ERα and PR were associated with higher inflammatory status, whereas FSHR detection demonstrated variable patterns among the studied groups. Conclusion: Pregnancy-associated periodontal disease is linked to differential detection of sex hormone receptors in gingival tissues. These molecular alterations may contribute to increased susceptibility to inflammation and periodontal tissue breakdown during pregnancy.